2005
DOI: 10.1103/physrevlett.94.157206
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Spin Fluctuations inNa0.75CoO2

Abstract: We report polarized- and unpolarized-neutron scattering measurements of magnetic excitations in single-crystal Na0.75CoO2. The data confirm ferromagnetic correlations within the cobalt layers and reveal antiferromagnetic correlations perpendicular to the layers, consistent with an A-type antiferromagnetic ordering. The magnetic modes propagating perpendicular to the layers are sharp, and reach a maximum energy of approximately 12 meV. From a minimal spin-wave model, containing only nearest-neighbor Heisenberg … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
103
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(116 citation statements)
references
References 25 publications
12
103
1
Order By: Relevance
“…3,4 The most interesting material in the Pauli metal regime is x ϳ 1 / 3 that exhibits an unexpected superconductivity upon further intercalation with water. 10 For 0.75Յ x Յ 0.84 in the Curie-Weiss metal regime, the onset of a long-range A-type antiferromagnetic ordering ͑Co-intraplane ferromagnetic coupling and Co-interplane antiferromagnetic coupling͒ at ϳ22 K has been indicated, [11][12][13] and the enhanced thermoelectric power due to large spin entropy has been found and explained for ϳ0.84. 14 Intriguingly, the other Curie-Weiss metal, x = 0.71, exhibits no magnetic ordering down to ϳ1.8 K. 3 The exactly half Na filled phase of x = 0.5 is the only compound that shows a metal-to-insulator transition ͑MIT͒ near ϳ51 K. 3,4,15,16 Indeed, the unique transport property for x = 0.5 had stimulated a remarkable number of associated studies, leading to the discovery that the room-temperature crystal structure of x = 0.5 shows an orthorhombic superlattice of ͱ 3a p ϫ 2a p ϫ c p ͑a p and c p , the hexagonal primitive cell parameters͒.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,4 The most interesting material in the Pauli metal regime is x ϳ 1 / 3 that exhibits an unexpected superconductivity upon further intercalation with water. 10 For 0.75Յ x Յ 0.84 in the Curie-Weiss metal regime, the onset of a long-range A-type antiferromagnetic ordering ͑Co-intraplane ferromagnetic coupling and Co-interplane antiferromagnetic coupling͒ at ϳ22 K has been indicated, [11][12][13] and the enhanced thermoelectric power due to large spin entropy has been found and explained for ϳ0.84. 14 Intriguingly, the other Curie-Weiss metal, x = 0.71, exhibits no magnetic ordering down to ϳ1.8 K. 3 The exactly half Na filled phase of x = 0.5 is the only compound that shows a metal-to-insulator transition ͑MIT͒ near ϳ51 K. 3,4,15,16 Indeed, the unique transport property for x = 0.5 had stimulated a remarkable number of associated studies, leading to the discovery that the room-temperature crystal structure of x = 0.5 shows an orthorhombic superlattice of ͱ 3a p ϫ 2a p ϫ c p ͑a p and c p , the hexagonal primitive cell parameters͒.…”
Section: Introductionmentioning
confidence: 99%
“…3,4,17 For 0.75Յ x Յ 0.84 within the ionic context ͑charge localization 15 ͒, it has been suggested that the existence of A-type magnetic ordering near ϳ22 K is rather unexpectedly high considering the dilute spin-half Co 4+ in the lattices. 12,13 The inelastic neutron scattering further indicated that the ferromagnetic intraplane and antiferromagnetic interplane exchange constants are nearly comparable, whereas a much smaller interplane magnitude was expected due to the lamellar structure of ␥-Na x CoO 2 . 12,13 To account for these unexpected magnetic properties, the possible effect of sodium-ordering induced superlattices and itinerant charges deviating from the ionic context has been proposed 12,13 although the detailed superlattices remain to be elaborated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The A-type spin fluctuations, i.e. intra-plane ferromagnetic and inter-plane antiferromagnetic fluctuations, are observed in Na 0.7 CoO 2 by inelastic neutron scattering experiments [3,4]. The intercalated water molecules may block the inter-plane antiferromagnetic couplings.…”
Section: A-type Spin Fluctuations Via 23 Na Nmrmentioning
confidence: 98%
“…Except the charge ordered insulator Na x CoO 2 with x ≈ 1/2, Na x CoO 2 and the hydrated compounds are itinerant electronic systems. For x ≈0.7, A−type spin fluctuations (in-plane ferromagnetic and out-of-plane antiferromagnetic spin fluctuations) [3,4] The side views of the crystal structures of a parent Na0.7CoO2, a Na-deintercalated Na0.35CoO2 and a bi layer hydrated Na0.35CoO2 · yH2O. Open arrows indicate soft chemical treatment.…”
Section: Introductionmentioning
confidence: 99%